Effect of Thermocycling on the Colour Stability of Aesthetic Restorative Materials: An in-vitro Spectrophotometric Analysis - Swastika Bhattacharya; Tina Puthen Purayil; Kishore Ginjupalli; Sandya Kini; Swathi Pai (Association of Support to Oral Health Research (APESB), 2022)
Objective: To compare the color stability of Cention N, Fuji IX GP Extra, and Fuji IX GP after thermocycling. Material and Methods: Ten discs of each material of dimension 10 x 1 mm were prepared using a split mold. The preparations of the specimens were done according to the powder/liquid ratio as recommended by the manufacturers [4.6:1, 3.4:1 and 3.6:1 for the groups I, II, and III, respectively]. After setting, the samples were retrieved, and the thickness of each specimen was measured using a micrometer at five different locations. The specimens with variations in thickness, porosity or cracks were discarded and thus not included in the study. The selected specimens were stored in distilled water for 24 hours prior to testing. The prepared specimens were thermocycled at 5°C and 55°C, with a dwell time of 15 seconds for 250 or 500 cycles. Subsequently, the color parameters of the discs were measured using a spectrophotometer. The data were analyzed using two way ANOVA test, and a p-value <0.001 was considered. Results: Thermocycling resulted in changes in the color of both Glass Ionomer cement and Cention N (p<0.001). Among the materials tested, Cention N showed superior color stability. Conclusion: Cention N exhibited better color stability compared to Glass ionomer cements.